Social Media Promotion Strategy Approach (Case Study of Ubud Monkey Forest Tourist Attraction’s Instagram Account) - Arie Yudhistira, Putu Gde (Institut Pariwisata dan Bisnis Internasional, 2021)
This study aims to determine the promotional strategies undertaken by Monkey Forest in promoting its tourist attraction. Monkey forest is one of the tourist attractions in Bali which is located in Gianyar regency. In its development, a promotional strategy must always be considered in promoting a destination. The promotion strategy referred to in this study is a promotion strategy through Instagram account. Nowadays Instagram is one of the social media that is very widely used. The method used in this research is descriptive qualitative method. Data collection methods were obtained from direct observation, interviews with the monkey forest and observation of promotional strategies on social media Instagram @monkeyforestsanctuaryubud. Interviews were conducted with one of the monkey forest managers named Mr. Dwija. Then the data is processed and described descriptively through writing and pictures. The result of this research is that Monkey Forest uses 5 promotional strategies, namely strategic planning, situation analysis, communication process analysis, IMC program planning and Monitoring and Evaluation